Implementation Of The Project Based Learning Model In Improving Football Learning Outcomes - Oman Hadiana; Nanan Abdul Manan; Sartono Sartono; Firman Adityatama; Yani Fitriyani (JUARA : Jurnal Olahraga, 2022)
This study aims to determine the effectiveness of the application of the project-based learning model to football learning outcomes. The research method used is a True experiment with a randomized posttest-only control group design. The research sample was 60 grade IX students of SMPN 4 Ciawigebang, Kuningan Regency, divided into two groups an experimental class of 30 students and 30 students for a control group. The sampling technique uses random cluster sampling. Research instruments to measure student football learning outcomes with passing-stoping tests (skills), attitude scales (affective), and knowledge tests in the form of questions (cognitive). The data analysis technique used is the independent sample test. The results showed that the application of the project-based learning model positively influenced student football learning outcomes in both psychomotor, affective, and cognitive aspects.